Spanish for gringos : shortcuts, tips, and secrets to successful learning - Harvey, William C. frey50; Meisel, Paul. (Hauppauge, NY : Barron's, 1999)
This informal self teaching course is for you if lack the time or patience for traditional language training. You'll learn key Spanish phrases and get tips that will help you comprehend the spoken language.
Issued in a clear plastic case containing 3 audio CDs.
Keywords: Spanish language -- English; Language -- Spanish